Glasatelier Flos: opkomst, ondergang en archivalische herleving - Van Puyvelde, Judith (Studies over de sociaaleconomische geschiedenis van Limburg, 2022)
Glass workshop Flos from Steyl (Tegelen) was operating between 1910 and 2017. This article shortly describes the history of this business and the vicissitudes of its archive, now conserved at the Centre for the Social History of Limburg (SHCL). It also highlights the multiple choices that archivists need to make when cataloguing historical collections.